Pengaruh Formula Pupuk Urea-Zeolit-Arangaktif terhadap pH, N-total, KTK tanah dan Residu Pb pada Tanah Tercemar Limbah Industri - Rija Sudirja; Santi Rosniawaty; Ade Setiawan; Rhendika Indra Yunianto (Fakultas Pertanian Universitas Padjadjaran, 2016)
One of the factors inhibiting the production of rice is not efficient in the use of fertilizers and ecosystem damage due to toxic hazardous materials such as heavy metals. the use of Urea, Zeolite, Activated charcoal based fertilizer is expected to increase the production of paddy rice crops in rice fields heavy metal contaminated. The experiment was conducted in the village of the District Linggar Rancaekek Regency Bandung from March to May 2015. The experiment used randomized block design with four single treatment, that is A = urea : zeolite (95:5), B = urea : zeolite : activated charcoal (50:45:5), C = urea : zeolite : activated charcoal (50:25:25), D = urea : zeolite (60:40), each with five replicates. Rice varieties used are Inpari 30. The results showed that administration RS fertilizer formula is proven to reduce the solubility of approximately 30% Pb and increases the cation exchange capacity (CEC) of the soil. RS fertilizer no real effect on pH and N-Total soils. Formulation urea : zeolite : activated charcoal (50:25:25) can decrease the solubility of Pb, while the CEC best demonstrated by the increase in formulation urea : zeolite : activated charcoal (50: 45: 5). Key words: heavy metals, RS fertilizer, wetland rice